Peningkatan Kualitas Sumber Daya Manusia di Lembaga Pendidikan Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Ismanto, Budi; Jaenudin, Jaenudin; Putri, Aldila Rahma (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Human resource quality is a key factor in achieving excellence in educational institutions. Many schools, particularly in developing or rural areas, face challenges in improving the skills and professionalism of their staff and organizational management. In response, a community service activity (PKM) titled